Saccharomyces boulardii exerts renoprotection by modulating oxidative stress, renin angiotensin system and uropathogenic microbiota in a murine model of diabetes - Abreu, Isabel Cristina Mallostro Emerich de; Albuquerque, Raquel Cristina Melo Ferreira de; Brandão, Ana Beatriz Pereira; Barssotti, Leticia; de Souza, Lívia Bruni; Ferreira, Fabiana Gomes; Oliveira, Lilian Caroline Gonçalves de; Yokota, Rodrigo; Sparvoli, Luiz Gustavo; Dias, Danielle da Silva; Salgado, Miguel Angel Castillo [UNESP]; Taddei, Carla; et al. (Elsevier, 2022)
Aims: We aimed to investigate whether Saccharomyces boulardii strain might exert renoprotective effects by modulating renal renin angiotensin system, oxidative stress and intestinal microbiota in streptozotocin-diabetic mice. Main methods: Thirty-six C57BL/6 male mice were divided into four groups: control (C), control + probiotic (CP), diabetes (D), diabetes + probiotic (DP). Diabetes was induced by one intraperitoneal injection of streptozotocin and Saccharomyces boulardii was administered by oral gavage for 8 weeks. Blood glucose, albuminuria and urinary volume were measured. Renal levels of angiotensin peptides (angiotensin I, II and 1–7) and the activities of angiotensin-converting enzyme (ACE) and ACE2 were determined, besides that, renal morphology, serotonin and dopamine levels and also microbiota composition were analyzed. Key findings: Probiotics significantly increased C-peptide secretion and reduced blood glucose of diabetic animals. Saccharomyces boulardii also improved renal antioxidant defense, restored serotonin and dopamine concentration, and activated the renin-angiotensin system (RAS) vasodilator and antifibrotic axis. The modulation of these markers was associated with a beneficial impact on glomerular structure and renal function of diabetic treated animals. The phenotypic changes induced by Saccharomyces boulardii were also related to modulation of intestinal microbiota, evidenced by the decreased abundance of Proteus and Escherichia-Shigella, considered diabetic nephropathy biomarkers. Significance: Therefore, probiotic administration to streptozotocin-induced diabetic mice improves kidney structure and function in a murine model and might represent a reasonable strategy to counteract nephropathy-associated maladaptive responses in diabetes.
Keywords: Albuminuria; Diabetic nephropathy; Oxidative stress; Renin-angiotensin system; Streptozotocin-diabetic mice; Uropathogenic microbiota